Critique of fantasy. the contest between B-genres - Rickels, Laurence A. (punctum books, 2020)
In the "Introduction; or, How Star Wars Became Our Oldest Cultural Memory" of the first volume of Critique of Fantasy, the gambit of a contest between science fiction and fantasy was already sketched out. J.R.R. Tolkien and C.S. Lewis aimed to separate the fantasy from the techno-science foregrounded in works by H.G. Wells, for example, and raise the fantasy or fairy-story to the power of an alternate adult literary genre. My study of the contest between the B-genres for ownership of the evolution of the social relation of art out of the condemned site of day dreaming required in the first place a reading apparatus, which the first volume derived from psychoanalytic theories of daydreaming's relationship to conscious thought, the unconscious, and artistic production as well as from their prehistory, the philosophies of dreams, ghosts, willing and wishing.